Pengaruh Likuiditas, Solvabilitas dan Profitabilitas Terhadap Financial Distress pada Bank Perkreditan Rakyat (BPR) - Marin Putri Muzdalifah; Lilis Setyowati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the effect of liquidity, solvency, and profitability on financial distress in BPR banking sector companies registered with the Financial Services Authority for the period 2020-2023. The data used in this study are secondary data in the form of annual financial reports. The sampling technique used in this study is the purposive sampling method with the number of banking sector companies used as samples being 255 BPR banks, but those that meet the criteria are 102 BPR banks. The analysis method used in this study is multiple linear regression analysis using the SPSS 26 program application. The results of this study indicate that liquidity does not affect financial distress, while solvency and profitability do affect financial distress.